PAKISTAN UNTUK MENANGANI PERDAGANGAN ANAK DI WILAYAH PERBATASAN - Milala, Cantika Putri Milna; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research analyses the countermeasures that Pakistan took to manage child trafficking, especially improvements that were made in its border security as the main focus of this research. This research is interesting to analyse because it shows that social factors, such as economic disparity, poor education and gender discrimination, can make huge impacts on how fast a crime grows. Especially transnational organized crime. Another intriguing factor this research is based on is that most of the victims of child trafficking in form of sexual exploitation are boys, which eliminated social stigmas that such crime only happens to girls.This is a qualitative research that applies document analysis method to examine data from journals, books, newspapers, and websites. This research use border security as a concept to give a more in-depth explanation about human trafficking. The perspective used is constructivism and national-state level analysis.This research shows that the strategies that Pakistan used were state-centric rather than people-oriented approaches. Some of the measures Pakistan took to increase its border security is by using a series of systems and programs to help security agencies detect activities that could potentially lead to trafficking. Pakistan also formed a special unit that guards immigration areas, passed laws that help identify human trafficking issues and also built fences across all of its borders.Â Keywords: Strategy, Child Trafficking, Transnational Organized Crime, Border Security, Human Security.Â